Concizumab restores thrombin generation potential in patients with haemophilia: Pharmacokinetic/pharmacodynamic modelling results of concizumab phase 1/1b data. Issue 1 (8th November 2018) - Eichler, Hermann; Angchaisuksiri, Pantep; Kavakli, Kaan; Knoebl, Paul; Windyga, Jerzy; Jiménez‐Yuste, Victor; Harder Delff, Philip; Chowdary, Pratima
Abstract : Introduction: Concizumab enhances thrombin generation (TG) potential in haemophilia patients by inhibiting tissue factor pathway inhibitor (TFPI). In EXPLORER3 (phase 1b), a dose‐dependent pharmacokinetic/pharmacodynamic (PK/PD) relationship was confirmed between concizumab dose, free TFPI and TG potential. Aim: Determine the association between concizumab exposure, PD markers (free TFPI; peak TG) and bleeding episodes to establish the minimum concizumab concentration for achieving sufficient efficacy. Methods: Free TFPI predictions were generated using an estimated concizumab‐free TFPI exposure‐response ( E max ) model based on concizumab phase 1/1b data for which simultaneously collected concizumab and free TFPI samples were available. Concizumab concentration at the time of a bleed was predicted using a PK model, based on available data for concizumab doses >50 μg/kg to ≤9 mg/kg. Peak TG vs concizumab concentration analyses and an E max model were constructed based on EXPLORER3 observations. Results: The E max model showed a tight PK/PD relationship between concizumab exposure and free TFPI; free TFPI decreased with increasing concizumab concentration. A strong correlation between concizumab concentration and peak TG was observed; concizumab >100 ng/mL re‐established TG potential to within the normal reference range. Estimated EC50 values for the identified concizumab‐free TFPI and concizumab‐TG potential models were very similar, supporting free TFPI as an important biomarker. A correlation between bleeding episode frequency and concizumab concentration was indicated; patients with a concizumab concentration >100 ng/mL experienced less frequent bleeding. The PK model predicted that once‐daily dosing would minimize within‐patient concizumab PK variability. Conclusion: Concizumab phase 2 trials will target an exposure ≥100 ng/mL, with a once‐daily regimen.